Using Honey on Debridement Wound Treatment for Post Necrotic Cellulitis Patients: Case Study - Riansyah, Alvi; Farhan, Zahara (Nursing Case Insight Journal, 2023)
Cellulitis is a health problem of the skin which occurs due to infection in the sub-cutaneous part of the skin. Cellulitis causes damage to tissue integrity, where this tissue damage requires further action, bacteria exposed to the sub-cutaneous area can cause widespread damage. Therefore, it is necessary to choose the right type of wound care in treating this disease. This case study aims to obtain the effect of applying wound care using honey for the recovery of debrided necrotic cellulitis wounds. The research used is a descriptive case study using nursing care and a literature review. Participants in this study were debrided necrotic cellulitis patients. This case shows that the application of wound care to patients with debridement necrotic cellulitis experienced improved wound recovery, indicated by the presence of adhesion on both sides of the tissue, the wound was pink, there were no signs of infection, there appeared to be a wound on the right leg. with the first wound area 1.5 x 2.3 cm with a depth of 1.5 cm and the second wound with an area of 1.5 x 4.5 cm with a depth of < 1 cm and the third wound 1.5 x 6.5 cm with a depth of 1 cm. -2 cm. Nurses can treat wounds in patients with debridement necrotic cellulitis using honey